Framework of trusted wireless sensor node platform for Wireless Sensor Network / Yusnani Mohd Yussoff - Mohd Yussoff, Yusnani (Institute of Graduate Studies, UiTM, 2013)
Wireless Sensor Networks (WSNs) have shown great promise as the emerging technology for data gathering from unattended or hostile environment. The advancement in micro-electro-mechanical sensor technology, wireless communication technology and the recent scavenging energy have gradually expanding the acceptance of WSN related applications. The design of sensors that are small, low cost, low power and combined with its unattended nature has made it more viable and indirectly promotes its popularity for future solutions in various real-life challenges. One of the most challenging yet important security issues in Wireless Sensor Network is in establishing trusted and secured communication between sensor node and base station. While the term trusted has been widely used referring to valid nodes in the group, this thesis refer the term trusted based on Trusted Computing Group (TCG) specifications. With limitations in the present solutions such as late discovery of invalid nodes such in Trust Management System and high energy consumption with external security chip due to the used of Trusted Platform Module chip; a Framework of a Trusted Wireless Sensor Node is presented…